The Structure of The Subject-Less Conventional Infinitives - Tjabaka, Lemohang Hilda; Morato-Maleke, ’Matšitso Eugenia (Selangor Humaniora Review, 2021)
The present study investigates the structure of the subject-less conventional infinitives at the Logical Form (LF) and Phonetic Form (PF). The study employed a constructivism paradigm, qualitative research approach, and case study design. Data were extracted from the previous English Ph.D. research studies conducted in the years 2010-2019 by both English native and non-native speakers. The study employed successive approximation analytic tools to analyse data, following the Minimalist Program (MP), which framed this study. The results revealed that the structure of the subject-less conventional infinitives varies. As a result, it can have an inflectional phrase (IP), tense phrase (TP), and verbaliser phrase (vP) structures.